2014
DOI: 10.1161/circulationaha.113.007765
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Acute I Kr Block Is Insufficient to Detect Torsades de Pointes Liability

Abstract: Background New drugs are routinely screened for acute IKr blocking properties thought to predict QT prolonging and arrhythmogenic liability. However, recent data suggest that chronic (hours) drug exposure to PI3 kinase (PI3K) inhibitors used in cancer can prolong QT by inhibiting potassium currents and increasing late sodium current (INa-L) in cardiomyocytes. We tested the extent to which IKr blockers with known QT liability generate arrhythmias through this pathway. Methods and Results Acute exposure to dof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
153
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(163 citation statements)
references
References 51 publications
8
153
0
2
Order By: Relevance
“…-transient decay and relaxation time (T2; measured from peak contraction to 20 % relaxation). On the other hand, inhibition of I Kr (with E-4031) or I Ks (with HMR1556) did not affect T2 duration in EHTs, in agreement with the unaltered APD reported in other studies [22]. In contrast, combined inhibition of I Kr and I Ks did produce a significant prolongation in relaxation time in rat EHTs.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…-transient decay and relaxation time (T2; measured from peak contraction to 20 % relaxation). On the other hand, inhibition of I Kr (with E-4031) or I Ks (with HMR1556) did not affect T2 duration in EHTs, in agreement with the unaltered APD reported in other studies [22]. In contrast, combined inhibition of I Kr and I Ks did produce a significant prolongation in relaxation time in rat EHTs.…”
supporting
confidence: 90%
“…For example, EHTs allow analysis of both acute and long-term/chronic applications of a compound. Recent work by Yang et al [22] has shown that several substances that were considered specific I Kr blockers can additionally cause an increase in late Na ? -current (I NaL ) when applied chronically and that this may contribute to their torsadogenic potential.…”
mentioning
confidence: 99%
“…44 This off-class effect was not explicitly investigated in our experiments. Nevertheless, combining dofetilide with a NCB would antagonize the proarrhythmic effect of I Na,L , potentially providing further antiarrhythmic action to this Na + /K + -channel combined block.…”
Section: Study Limitationsmentioning
confidence: 94%
“…It is a Vaughan Williams class III antiarrhythmic that causes a dose-dependent increase in both the atrial and ventricular refractory periods by selectively blocking the rapid component of the delayed rectifier potassium channel (I kr ) and increasing late sodium current (I Na-L ) in cardiac cells, thus prolonging the action potential in cardiac myocytes. 1 The Food and Drug Administration (FDA) first approved it in 1999 for converting to and maintaining sinus rhythm in patients with highly symptomatic AF and flutter of more than 1-week duration who were capable of being cardioverted. Although it is generally well tolerated with few clinical side effects, dofetilide requires inpatient initiation because of the known finite risk of Torsade de pointes (TdP).…”
mentioning
confidence: 99%